Heroical Poems in The Track of History Malay Culture: An Analysis of Heroical Values Warriors in The Contemporary Era: A Stylistic Study - Sarah Sinaga; Rosmawaty Harahap (Journal of Aceh Studies, 2024)
This research aims to analyze the heroic values in Malay heroic pantun and its relevance to the contemporary era through a stylistic approach. Pantun, as a form of traditional Malay oral literature, contains many cultural and moral values that can be used as references in understanding the concept of heroism in the context of Malay history and culture. This study uses a stylistic analysis method to identify and interpret the language style, structure, and symbols that reflect heroic values in the pantun. The results show that heroic pantun not only describes the courage and sacrifice of the warriors, but also highlights the importance of integrity, wisdom, and collective spirit in facing the challenges of the times. These values remain relevant and can be adapted in the context of the contemporary era, providing inspiration for the younger generation to appreciate and apply the principles of heroism in everyday life.